Immediate Implant Loading After Unsuccessful Orthodontic Treatment: A Case Report - , Antônio Ednardo de Souza Filho; , Lucas de Araújo Albuquerque; , Guilherme Salles Ottoboni; , Calebe Lamonier de Oliveira Costa Paiva; , Júlio César Monteiro Barbosa; , Joelson Pessoa Dantas; , Pedro Teylon Paiva Muniz; , Jamilly Vitória Souza Frota; , Francisco Danilo Madeira Araújo; , Poliana Lima Bastos (Archives of Current Research International, 2025)
Objectives: The objective of this study is to describe a patient with a history of recent orthodontic treatment and who presented internal resorption and mobility in element 12. Case Presentation: A 24-year-old female patient with a recent history of orthodontic treatment came to the dentist complaining of mobility in tooth 12. After a tomographic analysis, a large internal resorption was observed in tooth 12 and external resorption in teeth 13, 11, 21, 22 and 23, but without significant mobility. Therefore, it was decided to preserve the teeth that presented external resorptions, but without mobility, and extract tooth 12, due to its critical condition, and install an implant with immediate loading if the torque exceeded 35 N. The implant was placed with a torque of 60 N/cm2. Discussion: As is evident, one of the greatest advantages of combining the two techniques is the reduction in treatment time, maintenance of the morphology of soft and hard tissues, in addition to obtaining immediate aesthetics, which contributes to good acceptance of the technique by the patients treated. Conclusion: In this way, it was possible to restore function, aesthetics and quality of life to the patient.